Image Encryption on Mobile Phone using Super Encryption Algorithm - Emy Setyaningsih; Catur Iswahyudi; Naniek Widyastuti (Universitas Ahmad Dahlan, 2012)
Mobile phones have limited memory and computational resources. Modern encryption algorithms such as DES, AES, IDEA uses a complicated and complex algorithm, that are not suitable for image encryption on mobile phones. Necessary, it is tradeoff between speed, security, and flexibility. Problem to be investigated and resolved is how to get the image encryption algorithm which is simple yet safe, with the lightweight and efficient computing. The algorithm developed in this study was super-encryption algorithm that combines Playfair cipher and the Vigenere cipher. The experimental results show the cipher image histogram has a distribution of diversity and a significant difference to the plain image histogram, and frequency of occurrence of each intensity value in the histogram of cipher image is also uneven, which means can not provide clues to do statistical attack. The experimental results also showed a correlation between the elements of the image after encryption has decreased significantly. The average of quality encryption showed that the rate of change of image pixels is high enough so that cipher image difficult to identify. Tests on a cell phone showed that this algorithm requires only small computational resources. This shows that the algorithm is quite effective for image encryption on mobile phones.